The effect of air distrbuter shapes and its orifice properties in the aeration on fish ponds - Amal Elbendary Zaher Awad; Elsayed Moustafa Okasha; Mohamed Hashem Hatem; Yossry Bayoumy Abdelhay (Cairo : Amal Elbendary Zaher Awad, 2017)
This study was carried out during seasons of 2014, 2016 in a private farm located at Kafr El-Sheikh Governorate, Egypt. The aim of this research is to find out the best air shape distributors to supply fish ponds with the enough dissolved oxygen (concentration and saturation). To achieve the aim two experiments were carried out. In the first experiment seven forms( of air distributor shapes with Two different inter-holes diameters (1mm{u2013}2mm) and Two different distances between holes (15cm{u2013}30cm) were used in the absence of fish. the highest value of DO concentration was at the surface level of the tank with big spiral shape (S1) 8.81 mg/l then found at middle of the pond 8.5 mg/l by using (S1) then at down level of the pond 8.2 mg/l by (S1).The lowest value was at down level of the pond 4.52 mg/l by using control shape (S7) then at down level of the pond 5.71 mg/l by using big rectangle shape (S3) then at middle of the pond 5.5 mg/l by using control shape (S7). The best shape of air distributors was big spiral shape(without fish) .the semi intensive pond was higher than the other ponds in growing rate for cultivation tilapia fish by using big spiral shape with 1mm holes diameter and 15 cm distance between holes (with cultivating fish)
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Agricultural Engineering
Issued also as CD
Keywords: Aeration; Dissolved oxygen; Nile tilapia